Maternal Distress and Infant Social Withdrawal (ADBB) Following Infant Cardiac Surgery for Congenital Heart Disease. Issue 6 (November 2018) - Re, Jennifer M.; Dean, Suzanne; Mullaert, Jimmy; Guedeney, Antoine; Menahem, Samuel
Background: Mothers and infants are exposed to multiple stresses when cardiac surgery is required for the infant. This study reviewed infant responsiveness using a standardized objective observational measure of social withdrawal and explored its association with measures of maternal distress. Methods: Mother–infant pairs involving infants surviving early cardiac surgery were assessed when the infant was aged two months. Infant social withdrawal was measured using the Alarm Distress Baby Scale. Maternal distress was assessed using self-report measures for maternal depression (Edinburgh Postnatal Depression Scale), anxiety (Spielberger State-Trait Anxiety Scale), and parenting stress (Parenting Stress Index–Short Form). Potential associations between infant social withdrawal and maternal distress were evaluated. Results: High levels of maternal distress and infant social withdrawal were identified relative to community norms with a positive association. Such an association was not found between infant social withdrawal and the cardiac abnormality and surgery performed. Conclusion: The vulnerability of infants requiring cardiac surgery may be better understood when factors beyond their medical condition are considered. The findings suggested an association between maternal distress and infant social withdrawal, which may be consistent with mothers' distress placing infants subjected to cardiac surgery at substantially increased risk of social withdrawal. However, it is unclear to what extent infant withdrawal may trigger maternal distress and what the interactive effects are. Further research is warranted. Trialing a mother–infant support program may be helpful in alleviating distress and improving the well-being and outcomes for these families.